Terlipressin and albumin combination treatment in patients with hepatorenal syndrome type 2. Issue 4 (May 2019) - Nguyen-Tat, Marc; Jäger, Julia; Wilhelm Rey, Johannes; Nagel, Michael; Labenz, Christian; Wörns, Marcus-Alexander; Robert Galle, Peter; Uwe Marquardt, Jens
Background: Hepatorenal syndrome (HRS) is associated with a poor prognosis. In HRS type 1, loss of renal function is rapidly progressive, while HRS type 2 is characterised by chronic ascites and more moderately elevated renal parameters. While treatment with terlipressin/albumin is well established in type 1, its effectiveness in chronic HRS is less clear. Objective: The aim of this study was to evaluate the effectiveness of terlipressin/albumin treatment in patients with HRS type 2. Methods: All patients with a first episode of HRS between April 2013 and February 2016 were included in this observational study. Relevant clinical and laboratory parameters were recorded and patients were followed. Results: A total of 106 patients with HRS were included. With terlipressin therapy reversal of HRS types 1 and 2 was achieved in 48% and 46% of patients ( p  = 0.84) with relapse rates of 8% vs 50% ( p  = 0.001). Overall survival (OS) and survival free of liver transplantation (LTx) were similar in HRS types 1 and 2 ( p  = 0.69; p  = 0.64). In multivariate analysis response to treatment was independently associated with better OS in HRS type 2, in addition to established risk factors such as lower Model for End-Stage Liver Disease score, absence of hepatic encephalopathy and eligibility for LTx. Conclusion: A terlipressin treatment course seems to be justified in selected patients with HRS type 2, especially in countries and settings with long transplant waiting lists. In addition treatment response might also help to identify HRS type 2 patients with a more favourable outcome.